Stature, sex and weight estimation from footprint and foot outline dimensions of selected ethnic groups in Sarawak for forensic investigation - Khan, Hairunnisa Mohamad Anas (2018)
Footprints and foot outlines are physical and trace evidences commonly left at crime scene that can be used to establish stature, sex and body weight estimation. The aims of this study were to estimate population specific and sex-specific from footprints and foot outlines for stature and body weight as well as sex estimation from ridge density counting of selected ethnic groups residing in Sarawak state, East Malaysia i.e Iban, Bidayuh, Melanau and Lun Bawang. The stature, body weight, footprints and foot outlines were recorded following the standard procedure. The measured data for both stature and body weight estimation and also the counted footprint ridges from the eight defined size of 25mm2 were analysed with SPSS 20 statistical software for linear regression formulae derivation and also sexing potentials estimation by Receiver Operating Characteristic (ROC) curve. All of the footprint and foot outline lengths show significant (P<0.001) positive correlation with stature. One of the findings had shown extremely high correlation coefficient between footprint lengths of pooled samples (R: 0.861-0.887) with stature. In contrast, the positive significant (P<0.001) was only evident between breadth at ball of both footprint and foot outline dimensions with body weight. In footprints, the higher correlation coefficient was obtained between breadth at ball dimensions of pooled sample and body weight (R: 0.262 – 0.356). In sex estimation, the mean of footprint ridge density was significantly higher among females than males in all designated areas (P<0.05). One of the findings demonstrated total footprint ridge density was 91.6% from the right and 99.9% from the left foot respectively. In conclusion, footprints and foot outlines can help to determine criminal’s identity in forensic investigation.